Evaluating the effects of arthroscopic Bankart repair and open Latarjet shoulder stabilisation procedures on shoulder joint neuromechanics and function: a single-centre, parallel-arm trial protocol. Issue 1 (23rd February 2021) - Fox, Aaron; Bonacci, Jason; Gill, Stephen D; Page, Richard S
Abstract : Introduction: Shoulder instability injuries are common in sports involving collisions and overhead movements. Arthroscopic Bankart repair and the open Latarjet are two commonly used surgical stabilisation procedures. There is a lack of knowledge surrounding movement strategies, joint loading and muscle strength after each of these procedures. This study will compare: (1) shoulder joint neuromechanics during activities of daily living and an overhead sporting task; (2) shoulder range of motion; (3) shoulder strength; and (4) self-reported shoulder function and health status, between individuals who have undergone an arthroscopic Bankart repair versus open Latarjet. Methods and analysis: This is a prospective cohort, single-centre, non-randomised parallel arm study of surgical interventions for athletic shoulder instability injuries. Thirty participants will be recruited. Of these, 20 will have experienced one or more traumatic shoulder instability injuries requiring surgical stabilisation—and will undergo an arthroscopic Bankart repair or open Latarjet procedure. The remaining 10 participants will have no history of shoulder instability injury and act as controls. Participants will undergo baseline testing and be followed up at 3, 6 and 12 months. A two-way (group×time) analysis of variance with repeated measures on one factor (ie, time) will compare each outcome measure between groups across time points. Ethics and dissemination: This study was approved by the Barwon Health and Deakin University Human Research Ethics Committees. Outcomes will be disseminated through publications in peer-reviewed journals and presentations at relevant scientific conferences. Trial registration number: Australian and New Zealand Clinical Trials Registry (ACTRN12620000016932).